2022
DOI: 10.1101/2022.09.07.506986
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal enzymatic treatment to enhance the remodelling of multiple cartilage microtissues into a structurally organised tissue

Abstract: Scaffold-free tissue engineering strategies aim to recapitulate key aspects of normal developmental processes as a means of generating highly biomimetic grafts. Cartilage and fibrocartilaginous tissues have successfully been engineered by bringing together large numbers of cells, cellular aggregates or microtissues and allowing them to self-assemble or self-organize into a functional graft. Despite the promise of such approaches, considerable challenges still remain, such as engineering scaled-up tissues with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…For these and subsequent experiments, we used cells at passage 4 unless otherwise stated. Building on previous investigations, a one-time cABC treatment was applied at day 14 of chondrogenic culture to enhance collagen network maturation [71]. Following 5 weeks of in vitro culture, robust chondrogenesis of MPCs was observed within the MEW scaffolds, as evident by alcian blue staining for sGAG deposition (figure 3(B)).…”
Section: Biofabrication Of Structurally Organized and Phenotypically ...mentioning
confidence: 93%
“…For these and subsequent experiments, we used cells at passage 4 unless otherwise stated. Building on previous investigations, a one-time cABC treatment was applied at day 14 of chondrogenic culture to enhance collagen network maturation [71]. Following 5 weeks of in vitro culture, robust chondrogenesis of MPCs was observed within the MEW scaffolds, as evident by alcian blue staining for sGAG deposition (figure 3(B)).…”
Section: Biofabrication Of Structurally Organized and Phenotypically ...mentioning
confidence: 93%
“…Although the compressive properties of the resulting tissues were within the range of native values (90–160 kPa), the tensile properties, which are integral to tissue functionality, were still orders of magnitude below native values. It has previously been shown that the application of enzymes like chondroitinase ABC (cABC), which temporally remove sulfated glycosaminoglycansing (sGAGs) from the developing tissue, can enhance collagen fiber maturation and hence increase the mechanical properties of engineered cartilage and meniscus. , In the context of articular cartilage tissue engineering, it has also been shown that such treatments can support the formation of a more zonally organized collagen architecture . Therefore, the goal of this study was to determine the impact of such enzymatic treatment on the composition, structural organization and biomechanics of meniscal tissues that are engineered by inkjetting mesenchymal stem/stromal cells (MSCs) into MEW scaffolds with aligned pore architectures that support the development of structurally anisotropic fibrocartilaginous grafts.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 32 37 In the context of articular cartilage tissue engineering, it has also been shown that such treatments can support the formation of a more zonally organized collagen architecture. 38 Therefore, the goal of this study was to determine the impact of such enzymatic treatment on the composition, structural organization and biomechanics of meniscal tissues that are engineered by inkjetting mesenchymal stem/stromal cells (MSCs) into MEW scaffolds with aligned pore architectures that support the development of structurally anisotropic fibrocartilaginous grafts.…”
Section: Introductionmentioning
confidence: 99%